Enhancing the Precision of Machine Learning in the Library Profession - Akinola, Adeyemi Adewale (International Journal of Knowledge Content Development & Technology, 2025)
Machine learning has emerged as a transformative technology with the potential to revolutionize library services by enhancing precision and efficiency in various operational aspects. This study explores into the significance of machine learning in libraries, exploring its applications, challenges, and opportunities for optimization. The integration of machine learning algorithms enables libraries to streamline resource management, personalize user experiences, and automate tasks to meet evolving user demands. However, implementing machine learning in library operations poses challenges related to data collection, pre-processing, and ethical considerations. Strategies for enhancing precision through data labelling, annotation, and improving recommendation systems using machine learning are essential for maximizing the impact of these technologies. Evaluating the performance of machine learning models in library settings is crucial for assessing their effectiveness and ensuring reliable outcomes. Furthermore, ethical considerations must be prioritized to safeguard user privacy and mitigate algorithmic biases. Looking ahead, future trends and opportunities for machine learning in libraries hold promise for advancing service delivery, promoting innovation, and creating more user-centric library experiences.